DIMENSIONS OF METACOGNITION IN EDUCATIONAL ALTERNATIVES SUCH AS MONTESSORI, WALDORF, STEP BY STEP, AND REGGIO EMILIA - Marius Costel ESI (International Journal of Social and Educational Innovation)
When we talk about educational alternatives, our attention must focus on the main epistemic approaches through which the learning process takes shape. In such a context, we can speak of an approach that prioritizes reflection, personalized and individualized learning, as well as flexible learning. Within this explanatory framework, the aim of this paper is to analyze the extent to which the strategies specific to educational alternatives can be correlated with the concept of metacognition. Thus, we are interested in identifying the similarities and differences among these alternatives and how they can be extrapolated to the dimension of metacognition. Consequently, we will explore the main aspects of metacognition within the scientific context of educational alternatives such as Montessori, Waldorf, Step by Step, and Reggio Emilia.